Climate-Controlled Coastal Deposition of the Early Permian Liangshan Formation in Western South China - Liu, Ao; Yang, Jianghai; Cheng, Liang; Ren, Juntong (Frontiers in Earth Science, 2022)
During the late Paleozoic ice age, tropical coastal depositions have been widely linked to high-frequency sea-level variations, but their linkage with the associated climate change was not fully understood. In the Early Permian two deglaciations occurred in the late Sakmarian and late Artinskian, respectively. During the late Artinskian deglacial warming and transgression, there developed coal-bearing siliciclastic successions of the Liangshan Formation in South China. Three facies associations were recognized from the Liangshan Formation successions in western South China and ascribed to coastal alluvial plain, estuarine and deltaic environments. Detailed analysis of sedimentology, paleosol morphology, and sandstone petrology suggest a relatively dry to wet climate shift and estuarine to deltaic facies transition in the lower Liangshan Formation. This climate shift and facies transition can be temporally correlated based on regional stratigraphic correlations, though precise age constraints are needed to test this correlation. The estuarine interval of the lowest Liangshan Formation signified a rapid transgression during the late Artinskian deglaciation and likely formed during a relatively arid climate with locally small fluvial systems, which provided limited sediment supply. The subsequent transition to and initiation of deltaic deposition was broadly associated with the inferred climate shift and could be primarily resulted from a climate wetting induced great increase in sediment supply, irrespective of the deglacial sea-level rise.